2005
DOI: 10.1111/j.1440-1746.2005.03875.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological alterations in pregnant women with acute hepatitis E

Abstract: These results show the existence of a Th2 bias in pregnant women with acute hepatitis E. The role of this Th2 bias in the greater severity of hepatitis E among pregnant women needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 22 publications
2
87
1
1
Order By: Relevance
“…To address the role of the CMI response in HEV infection, a quantitative assay for measuring HEV-specific CMI responses is needed. Prior reports examined T cell proliferation Naik et al, 2002;Pal et al, 2005;Srivastava et al, 2007) or flow cytometry (Srivastava et al, 2007) as a surrogate marker for CMI responses to HEV, however, the sensitivity and specificity of these assays were low. During the last ten years, highly sensitive IFN-γ ELISPOT assays have been used successfully for measuring the CMI responses in different diseases (Dheda et al, 2005;Liu et al, 2006;Sun et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the role of the CMI response in HEV infection, a quantitative assay for measuring HEV-specific CMI responses is needed. Prior reports examined T cell proliferation Naik et al, 2002;Pal et al, 2005;Srivastava et al, 2007) or flow cytometry (Srivastava et al, 2007) as a surrogate marker for CMI responses to HEV, however, the sensitivity and specificity of these assays were low. During the last ten years, highly sensitive IFN-γ ELISPOT assays have been used successfully for measuring the CMI responses in different diseases (Dheda et al, 2005;Liu et al, 2006;Sun et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has suggested that CMI responses and T h1 /T h2 cytokine profiles in pregnant women are highly involved in HEV morbidity (Pal et al, 2005). To address the role of the CMI response in HEV infection, a quantitative assay for measuring HEV-specific CMI responses is needed.…”
Section: Discussionmentioning
confidence: 99%
“…36 The reason underlying the association of hepatitis E and pregnancy is unknown, though immunological or hormonal factors have been proposed. [39][40][41][42] Hepatitis E during pregnancy is also associated with prematurity and low birth weight. 43 The children born to such mothers frequently suffer from hypoglycemia and jaundice, and have an increased perinatal mortality.…”
Section: Relationship Of Hepatitis E With Host Characteristics Inclumentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] However, few studies investigated T-cell immunity in HEV infection. Some groups have analyzed HEV-specific cellular immune responses by screening potential T-cell epitopes in the open reading frame (ORF)2 and 3 regions of HEV describing HEV-specific lymphoproliferative responses in patients with acute hepatitis E. 25,26 In addition, pregnant women with acute HEV infection showed a Th2-biased T-cell response 27 and a stronger reactivity against HEV ORF2 and ORF3 proteins was associated with a milder course of disease in acute and fulminant hepatitis E. 28 However, these studies had limitations, as usually only one functional readout was applied and CD4þ and CD8þ T-cell responses were not distinguished. Moreover, and importantly, no study until now has addressed the role of T-cell responses in resolving and chronic HEV infection.…”
mentioning
confidence: 99%